FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT BERWIRAUSAHA PADA MAHASISWA PROGRAM STUDI PENDIDIKAN EKONOMI FKIP UNIVERSITAS RIAU - Sari Gustina; Sakdanur Nas; Hardisyem Syabrus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrak: Many college graduates are unemployed because of the level of competition in applying for a job higher. One of the efforts made by universities University of Riau in particular, is to educate students and prepare graduates to study entrepreneurship and make entrepreneurship as part of the curriculum given at the University of Riau. The purpose given these courses so that students can have a soul or characteristics of entrepreneurship and cultivate their interests and talents. In an effort to foster interest in entrepreneurship, it is first important to know the factors that influence the onset of that interest. Factors that affect the interest in entrepreneurship can be developed so that interest can be transformed into an independent business. Factors that affect the interest in entrepreneurship, there are two factors: internal factors and external factors, internal factors which include income, self-esteem and feelings of pleasure while External factors include family, community, and educational opportunities. This study aims to determine the influence of income, self-esteem, a sense of excitement, family, community, and educational opportunities to entrepreneurial interest on student of Economics Education FKIP Riau University with 42 sample obtained using purposive sampling. Data analysis techniques used in this research is multiple linear regression analysis, hypothesis testing simultaneously (test F), partial regression coefficient test (t test) and test the coefficient of determination (r2 adjusted). The research showed that There are significant effect between income, feelings of pleasure, society and education simultaneously and partially on the interest of entrepreneurship in students of Economic Education FKIP Riau University and There is no significant effect between self-esteem, family environment and the opportunities it partially on the entrepreneurial interest on student of Economics Education FKIP Riau University.Keywords: Interest in entrepreneurship, Income, Self-Esteem, afterglow, FamilyEnvironment, Environmental Society, Opportunities and Education